Buildings in society : international studies in the historic era - Thomas, Liz; Campbell, Jill (Archaeopress Publishing Ltd, 2018)
Presents a series of papers reflecting the latest approaches to the study of buildings from the historic period. This volume does not examine buildings as architecture, rather it adopts an archaeological perspective to consider them as artefacts, reflecting the needs of those who commissioned them.